Transfer of Inhaled Cannabis Into Human Breast Milk. Issue 5 (May 2018) - Baker, Teresa; Datta, Palika; Rewers-Felkins, Kathleen; Thompson, Heather; Kallem, Raja R.; Hale, Thomas W.
Abstract : OBJECTIVE: To evaluate the transfer of delta-9-tetrahydrocannabinol and its metabolites into human breast milk after maternal inhalation of 0.1 g cannabis containing 23.18% delta-9-tetrahydrocannabinol. METHODS: In this pilot pharmacokinetic study, breast milk samples were collected from mothers who regularly consumed cannabis, were 2–5 months postpartum, and exclusively breastfeeding their infants. Women were anonymously recruited for the study. After discontinuing cannabis for at least 24 hours, they were directed to obtain a baseline breast milk sample, then smoke a preweighed, analyzed, standardized strain of cannabis from one preselected dispensary, and collect breast milk samples at specific time points: 20 minutes and 1, 2, and 4 hours. Quantification of delta-9-tetrahydrocannabinol and its metabolites in these collected breast milk samples was performed by high-performance liquid chromatography tandem mass spectrometry. RESULTS: A total of eight women were enrolled. Most were occasional cannabis smokers and one a chronic user. Delta-9-tetrahydrocannabinol was detected at low concentrations at all the time points beyond time zero. No metabolites were detected at any time point. Delta-9-tetrahydrocannabinol was transferred into mother's milk such that exclusively breastfeeding infants ingested an estimated mean of 2.5% of the maternal dose (the calculated relative infant dose=2.5%, range 0.4–8.7%). The estimated daily infant dose was 8 micrograms per kilogram per day. CONCLUSION: This study documents inhaled delta-9-tetrahydrocannabinol transfer into the mother's breast milk. Low concentrations of delta-9-tetrahydrocannabinol were detected. The long-term neurobehavioral effect of exposure to delta-9-tetrahydrocannabinol on the developing brain is unclear. Mothers should be cautious using cannabis during pregnancy and breastfeeding. Abstract : After a standardized maternal dose of 23.18 mg inhaled cannabis, major metabolite delta-9-tetrahydrocannabinol is transferred into mother's milk such that an exclusively breastfeeding infant ingests an estimated mean 2.5% (range 0.4–8.7%) of the maternal dose.